Antifungal Activity of a Hydroethanolic Extract From Astronium urundeuva Leaves Against Candida albicans and Candida glabrata - Bonifácio, Bruna Vidal; Vila, Taissa Vieira Machado; Masiero, Isadora Fantacini; da Silva, Patrícia Bento; da Silva, Isabel Cristiane; de Oliveira Lopes, Érica; dos Santos Ramos, Matheus Aparecido; de Souza, Leonardo Perez; Vilegas, Wagner; Pavan, Fernando Rogério; Chorilli, Marlus; Lopez-Ribot, José Luis; et al. (Frontiers in Microbiology, 2019)
We have previously reported on the activity of different extracts from Astronium sp. against Candida albicans, with the hydroethanolic extract prepared from leaves of A. urundeuva, an arboreal species widely distributed in arid environments of South America and often used in folk medicine, displaying the highest in vitro activity. Here we have further evaluated the antifungal activity of this extract against strains of C. albicans and C. glabrata, the two most common etiological agents of candidiasis. The extract was tested alone and loaded into a nanostructured lipid system (10% oil phase, 10% surfactant and 80% aqueous phase, 0.5% Poloxamer 407®). In vitro susceptibility assays demonstrated the antifungal activity of the free extract and the microemulsion against both Candida species, with increased activity against C. glabrata, including collection strains and clinical isolates displaying different levels of resistance against the most common clinically-used antifungal drugs. Checkerboard results showed synergism when the free extract was combined with amphotericin B against C. albicans. Serial passage experiments confirmed development of resistance to fluconazole but not to the free extract upon prolonged exposure. Although preformed biofilms were intrinsically resistant to treatment with the extract, it was able to inhibit biofilm formation by C. albicans at concentrations comparable to those inhibiting planktonic growth. Cytotoxicity assays in different cell lines as well as an alternative model using Artemia salina L. confirmed a good safety profile of the both free and loaded extracts, and an in vivo assay demonstrated the efficacy of the free and loaded extracts when used topically in a rat model of vaginal candidiasis. Overall, these results reveal the promise of the A. urundeuva leaves extract to be further investigated and developed as an antifungal.